Assessing Innovation in Data Security and Regulatory Compliance: Implications for Perceived Cybersecurity and Service Reputation in the Cryptocurrency Exchange Sector - Rahman, Farrel Naufal; Hariadi, Melia Famiola (Journal Integration of Management Studies, 2025)
As Indonesia's digital economy continues to expand rapidly, fintech platforms—particularly those in the cryptocurrency exchange sector—face mounting cybersecurity challenges that directly affect customer trust and service reputation. This study examines how digital innovation in data security and adherence to regulatory frameworks influence service reputation, with perceived customer cybersecurity acting as a mediating factor. Adopting an explanatory quantitative approach using Structural Equation Modelling-Partial Least Squares (SEM-PLS), data were collected from users of a leading Indonesian crypto-asset platform. The results indicate that both technological innovation and compliance with data protection and financial regulations contribute meaningfully to users' perceptions of cybersecurity. In turn, these perceptions significantly shape customer satisfaction, trust, and loyalty—core components of service reputation. The findings highlight that perceived cybersecurity functions as a psychological bridge, connecting a company's technical and legal initiatives with its broader reputational outcomes. The study underscores the importance of not only implementing secure and compliant systems but also communicating them transparently to sustain trust and resilience in a post-breach digital environment.